Impact of Corporate Social Responsibility on Firm Performance with Moderating Effect of Earning Management - Tariq Jami; Dr. Khushnood Ahmad; Dr. Tanveer Ahmad, (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2024)
The purpose of this study is to investigate the impact of corporate social responsibility on firm performance with a moderating effect of earnings management. The study used a sample of 150 non-financial listed firms on the Pakistan Stock Exchange (PSX). The study covered the period from 2012 to 2022, and the study used the stratified random technique for sampling. The data were analyzed through descriptive statistics, regression analysis, and the multiple linear regression method. The study findings reveal that corporate social responsibility has a significant impact on firm performance, and this relationship is also moderated by earnings management. It can provide helpful information for investors and policymakers in this regard.